Kardiochirurgia wad wrodzonychGiant diverticulum of the right atrium - Sharma, Girish; Augustyn, Cyprian; Mieczyński, Mariusz; Pawelec-Wojtalik, Małgorzata; Chodorowska, Anna; Wronecki, Krzysztof; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Congenital diverticula of the right atrium are very rare malformations. Frequently they are asymptomatic and are detected accidentally on a chest radiograph or during the autopsy. We present a case of symptomatic giant diverticulum of the right atrium in a 3-month old female. Major symptoms were atrial fibrillations with low cardiac output leading to cardiac arrest. She was qualified for urgent operation. To avoid bleeding hazard abdominal vessels were cannulated and atrioplasty performed in deep hypothermia. In the post-operative period the patient remained in sinus rhythm and the heart size normalized.